2022
DOI: 10.1002/hsr2.759
|View full text |Cite
|
Sign up to set email alerts
|

Under‐prescription of medications in older adults according to START criteria: A cross‐sectional study in Lebanon

Abstract: Background and Aims Under‐prescription is defined as the exclusion of medications indicated for the treatment of certain conditions without any rationale for not prescribing them. The under‐prescription of medications is highly prevalent among older adults (≥65 years) receiving polypharmacy. This study aimed to assess the prevalence of the under‐prescription of medications using the Screening Tool to Alert to Right Treatment (START) criteria version 2 and to identify the predictors of having poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Administration of Statin (45.7%in frails) (71.4% in controls), ACEI (34.3%in frails) (62.9% in controls) and Aspocid (34.3%in frails) (60% in controls) were signi cantly less frequent in frail group. Our study agreed withÖZTÜRK et al, 2023, Yoshimura et al, 2022, Hanna et al, 2022, that frail elderly take fewer protective medications. This could be due to nancial burden, drugs adverse effect, care giver issues, advanced age, negative believes about usefulness of such medication in advanced age and its role in decreasing mortality/ morbidity.…”
supporting
confidence: 91%
“…Administration of Statin (45.7%in frails) (71.4% in controls), ACEI (34.3%in frails) (62.9% in controls) and Aspocid (34.3%in frails) (60% in controls) were signi cantly less frequent in frail group. Our study agreed withÖZTÜRK et al, 2023, Yoshimura et al, 2022, Hanna et al, 2022, that frail elderly take fewer protective medications. This could be due to nancial burden, drugs adverse effect, care giver issues, advanced age, negative believes about usefulness of such medication in advanced age and its role in decreasing mortality/ morbidity.…”
supporting
confidence: 91%
“…This study results were in agreement with earlier studies which showed that omissions of cardiovascular medications represent the most common omissions among geriatric patients with and without cancer. 21 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…This study results were in agreement with earlier studies which showed that omissions of cardiovascular medications represent the most common omissions among geriatric patients with and without cancer. 21,32,33 The limitations of this study include the retrospective nature of the medical record evaluations, even though researchers evaluated the medical charts carefully to ensure a high level of accuracy for patient data extraction. Second, some factors such as performance status of the patients and over the counter and self-medications taking which could contribute to PIMs and POMs occurrence were not evaluated in this study.…”
mentioning
confidence: 99%
“…At the same time, the explicit method is direct, based on criteria that are usually elaborated upon through expert consensus based on the literature review. 9 Criteria from different countries are used to classify and describe the risks of PIM use, 10 , 11 so part of these criteria are based on the Beers criterion and local differences regarding the drugs approved for use.…”
Section: Introductionmentioning
confidence: 99%